2021
DOI: 10.3389/fsurg.2021.686930
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surgical Outcomes Between Separation Surgery and Piecemeal Spondylectomy for Spinal Metastasis: A Retrospective Analysis

Abstract: Objective: This study aimed to compare the outcomes between piecemeal spondylectomy and separation surgery for patients with spinal metastasis.Summary of Background Data: Piecemeal spondylectomy and separation surgery are two widely-used treatment options for spinal metastasis. However, no studies have compared the surgical outcomes between both treatment modalities.Methods: Patients with spinal metastasis who underwent piecemeal spondylectomy or separation surgery between August 2017 and April 2020 at our spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…Traditionally, complication rates are higher in patients undergoing corpectomy compared to separation surgery, but both surgeries have wide ranges reported in the literature. The complication rate in this study (n=9, 14.2%) was lower than the corpectomy complication rates reported by Gokaslan et [40,41]. No patients had long-term surgical complications nor did any patients die within 30 days of surgery for reasons related to their surgery.…”
Section: Complicationscontrasting
confidence: 64%
“…Traditionally, complication rates are higher in patients undergoing corpectomy compared to separation surgery, but both surgeries have wide ranges reported in the literature. The complication rate in this study (n=9, 14.2%) was lower than the corpectomy complication rates reported by Gokaslan et [40,41]. No patients had long-term surgical complications nor did any patients die within 30 days of surgery for reasons related to their surgery.…”
Section: Complicationscontrasting
confidence: 64%
“…Ten studies were retrospective, including a total of 482 patients, and three studies were prospective studies of 179 patients. Eleven studies reported the sex proportion of included patients, and of these, 58 % were male [18] , [19] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] . Six studies were conducted in the United States, five in China, and two in Japan.…”
Section: Resultsmentioning
confidence: 99%
“…In the scope of our project, it was difficult to conduct subgroup analysis comparing hybrid therapy with other treatments because there were only single studies comparing it directly with other treatments. Among included studies, one study showed direct comparison of LC rate between hybrid therapy and SABR alone [24] , another showed comparison between hybrid therapy and total en bloc spondylectomy [18] , and the other showed comparison between hybrid therapy and piecemeal spondylectomy [31] . Further analysis will become possible if additional studies that directly compare hybrid therapy with the others are published in the future.…”
Section: Limitationsmentioning
confidence: 99%
“…Due to the limitation of focus debridement, the safety of separation surgery is similar or better than that of other surgical treatments. Xu et al 43 reported 55 patients treated with piecemeal spondylectomy or separation surgery. Patients underwent separation surgery had less blood loss (1165.52 ± 307.38 mL vs 1784.62 ± 833.64 mL), less complications (15.38% vs 3.45%), and shorter operation time (3.73 ± 1.15 h vs 4.76 ± 0.93 h) than piecemeal spondylectomy.…”
Section: Complicationsmentioning
confidence: 99%